Sistem Pelayanan Panti LRPPN Bhayangkara Indonesia: (Kec. Medan Helvetia, Kota Medan) - Asri Adilah; Muhammad Revi Sahbani; Tasya Novriyanti; Yosi Yarli; Syifa Sabina Febriani (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Drug abuse (Narcotics, Psychotropics and Addictive Substances) is a case that is increasing day by day both in quantity and quality. This is a problem that cannot be taken lightly because most drug cases are found in young people, the next generation of the nation. This drug abuse certainly results in drug dependence, which according to WHO is defined as a condition of periodic or chronic intoxication resulting from the repeated use of drugs, either naturally or synthetically. The high number of cases of drug threats can be caused by a lack of strategies in self-management, wrong expectations and cognition, causing a deficiency in taking steps to control one's emotions and a person's inability to stand up in the midst of the many difficulties they face. This mini-project research aims to find out about the social welfare service system for drug users at the BI LRPPN Rehabilitation Institution. The method used in this practice uses the Case Work Method for treatment based on Therapeutic Community (TC) which was popularized by Skidmore. This method is commonly used in rehabilitation institutions and is considered effective in the recovery process for residents. This is because the TC concept itself offers health-based, spiritual, and psychological services that include cognitive and behavioral aspects. The TC method also hones every resident to continue to be responsible, both to themselves, the group and the surrounding environment.